2016
DOI: 10.1007/s00213-016-4307-9
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal response to methylphenidate across multiple fMRI procedures in cocaine use disorder: feasibility study

Abstract: Rationale The indirect dopamine agonist methylphenidate remediates cognitive deficits in psychopathology, but the individual characteristics that determine its effects on the brain are not known. Objectives We aimed to determine whether targeted dopaminergically-modulated traits and individual differences could predict neural response to methylphenidate across multiple functional magnetic resonance imaging (fMRI) procedures. Methods We combined neural measures from three separate procedures (two inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…At best, there is inconsistent evidence for stimulants and other pharmacotherapies in patients with cocaine dependence [12, 19, 21, 26]. These findings are supported by an MRI study demonstrating reduced activation of the dorsolateral prefrontal cortex in response to MPH intake in cocaine-using patients in comparison to controls [43]. Thus, MPH may cause beneficial but generally modest effects in cocaine users.…”
Section: Discussionmentioning
confidence: 99%
“…At best, there is inconsistent evidence for stimulants and other pharmacotherapies in patients with cocaine dependence [12, 19, 21, 26]. These findings are supported by an MRI study demonstrating reduced activation of the dorsolateral prefrontal cortex in response to MPH intake in cocaine-using patients in comparison to controls [43]. Thus, MPH may cause beneficial but generally modest effects in cocaine users.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that developing novel strategies to improve PES in laboratory settings via training or medication [e.g. the dopaminergic agonist methylphenidate, which has shown initial promise in modulating behavior during tasks of response inhibition reported here (Li et al ., ; Moeller et al ., , )] could lead to corresponding improvements in behavioral adaption in those diagnosed with SUD. Supporting this view are a small number of studies that reported correlations between PES and adaptive change in task performance, although these findings have been mixed (see Table ) and at times nuanced [e.g.…”
Section: Discussionmentioning
confidence: 99%